Estimation of BMD using Portable Heel Ultrasound Bone Densitometer in a District Hospital of Northern Bangladesh- A pilot study - Naher, Fatema Kamrun; Shuha, Sadia Mahfuz (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Bone is a living tissue. Solid matters of the bone are composed of minerals and organic matter. Peak Bone Mineral Density (BMD) is maximum during growth in skeleton system. There is variation of range for peak BMD, influenced by genetic and environmental factors. In women, peak bone mass is achieved by the 2nd decade and begins to decrease after 35 years of age. Osteopenia and osteoporosis are the major bone morbidities in women and usually occurs after menopause. Objective: To identify the BMD in people of a community of a District of Bangladesh. Methodology: This cross-sectional study was done at an out-patient department in a District hospital, in February2022. Data were collected by conducting individual interview through a structured questionnaire. A total 50 cases were included, both sexes of 18-62 years of age. The T-score data were collected and BMD were presented in systematic manner based on WHO guideline. After collection, data were analyzed, tabulated and presented. Results: Among study population 32 were female and 18 were male. BMD status were normal in 70% cases and low bone mass were 30%, there was no osteoporosis. Male are suffering from low bone mass than female. Low bone mass is slightly higher among old women and working women. Conclusions: Bone health status in this population, 70% is normal Bangladesh J Obstet Gynaecol, 2023; Vol. 38(2): 92-95